Animation : critical and primary sources vol 4 - Pallant, Chris (New York : Bloomsbury Academic, 2021)
"Animation: Critical and Primary Sources is a major multi-volume work of reference that brings together seminal writings on animation studies. Gathering historical and contemporary texts from a wide-ranging number of sources, the volumes provide a key resource in understanding and studying the past and future directions of animation studies. The four volumes thematically trace animation studies from its many definitions, or a lack thereof, to the institutional nature of animation production, to establishing greater space within animation discourse for the consideration of broadcast and interactive animation, and finally, giving greater contextual understanding of the field of animation studies, by focusing on 'Authorship', 'Genre', 'Identity Politics', and 'Spectatorship', thus enabling readers to engage more deeply with the ideas discussed in the final volume. Ordering the collection in this way avoids imposing an overly simplistic chronological framework, thereby allowing debates that have developed over years (and even decades) to stand side by side. Each volume is separately introduced and the essays structured into coherent sections on specific themes"--
v. 1. Definition and form -- v. 2. Content -- v. 3. Context -- v. 4. Key individuals.
Includes bibliographical references and index.
Keywords: Animated films -- History and criticism; Animation (Cinematography) -- History; Animators